French Immersion: Are We Getting our Just Desserts? - Carlson Berg, Laurie (Revue de l'Université de Moncton, 2007)
AbstractIn this paper, I will not focus my comments on the relative merit of the various potential entry points into French Immersion. Rather, I will discuss some of the benefits of bilingualism and explain my thinking about matters I believe to be equity issues in French Immersion. My perspective is that of a mother attempting to make informed decisions about her children’s schooling options. While I raise some pointed questions, I do so with humility as I am only beginning to familiarize myself with the related literature.